The farsighted stability of global trade policy arrangements - Stefan Berens; Lasha Chochua; Gerald Willmann (Bielefeld University, Faculty of Business Administration and Economics, 2021)
We study the stability of trade policy arrangements under two regulatory scenarios, with/without PTAs. Unlike previous papers, we consider an extensive set of trade policy constellations and allow for unlimited farsightedness of negotiating parties. We find global free trade (GFT) to be uniquely stable under symmetry, with/without PTAs. When two countries are smaller(larger) than the third, availability of PTAs decreases (increases) the stability of GFT. Away from symmetry, GFT is not attainable, and without PTAs the non-cooperative MFN regime is the only stable outcome. The effect of (dis-)allowing PTAs thus depends on the size asymmetry of countries.
urn:nbn:de:0070-pub-29562204
Keywords: F13; F55; 380; Trade Policy Arrangements; Stability; Unlimited Farsightedness